2006
DOI: 10.1186/1472-6831-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and socio-behavioral correlates of tooth loss: a study of older adults in Tanzania

Abstract: BackgroundFocusing 50 year olds and above, this study assessed the frequency, extent and correlates of tooth loss due to various reasons. Frequency and correlates of posterior occluding support was also investigated.MethodA cross-sectional household survey was conducted in Pwani region and in Dar es Salaam in 2004/2005. One thousand and thirty-one subjects, mean age 62.9 years participated in a clinical examination and completed interviews.ResultsThe prevalence of tooth loss due to any reason was 83.5 %, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
58
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 32 publications
19
58
1
8
Order By: Relevance
“…Some researchers reported socio-economic inequalities were related to oral health loss. [15][16][17][18] The perceptions about dental disease of the respondents were 97.0% and only 3.0% respondent did not have idea about dental diseases.The respondents believe that improper cleaning of teeth and mouth 64.94%, taking of excessive sweets 21.64% and residual food in the oro-dental cavity 13.40% are responsible for dental diseases. Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some researchers reported socio-economic inequalities were related to oral health loss. [15][16][17][18] The perceptions about dental disease of the respondents were 97.0% and only 3.0% respondent did not have idea about dental diseases.The respondents believe that improper cleaning of teeth and mouth 64.94%, taking of excessive sweets 21.64% and residual food in the oro-dental cavity 13.40% are responsible for dental diseases. Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents. Some study revealed that Dental and oral health are affected by diet and certain aspects of lifestyle [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations